Psychopathy as a predisposition to lie hedonistically - Rassin, Eric (Psychology, crime & law, 2025)
Excessive lying is generally considered to be a hallmark of psychopathy. Meanwhile, the empirical evidence for the association between psychopathy and lying is somewhat limited. In the present study, non-clinical volunteers completed a measure of psychopathy, and were then brought in an experimental situation (a puzzle task) in which they could opt to lie for potential personal gain (i.e. monetary reward). Findings suggest that 19% of participants (i.e. 31 out of 166) lied about their performance in the puzzle task, thus increasing their likelihood of gaining additional reward. These lying participants scored significantly higher on psychopathy than did their honest peers. Thus, the findings support the hypothesis that psychopathy is characterised by deceitful behaviour. Particularly, psychopathic boldness was associated with lying.